Genetic polymorphism of Plasmodium falciparum circumsporozoite protein in Kigali, Rwanda - Fankem, Sandra Noukimi; Mbonimpa, Jean-Bosco; Kalimba, Edgar Mutebwa; Diallo, Mariama Telly; Souopgui, Jacob (Frontiers in Parasitology, 2025)
IntroductionMalaria remains a major public health challenge across sub-Saharan Africa, with Plasmodium falciparum responsible for the vast majority of cases and deaths. In Rwanda, although control measures have led to significant progress, malaria continues to be endemic, with urban centers like Kigali experiencing continuous transmission. With the recent rollout of malaria vaccines such as RTS,S and R21, understanding the genetic variability of vaccine-targeted antigens is essential for anticipating and enhancing vaccine performance.MethodsThis study investigated the genetic diversity of the Plasmodium falciparum circumsporozoite protein (Pfcsp) gene among 245 clinical isolates collected between October 2021 and June 2023 at King Faisal Hospital, a referral center in Kigali, Rwanda. PCR amplification of the csp locus was performed, and the resulting amplicons were sequenced using Oxford Nanopore Technology (ONT) employing the R10.4 flow cell chemistry, allowing for high-resolution haplotype reconstruction and detection of polymorphic sites across the gene.ResultsA total of 48 distinct haplotypes were identified, indicating high haplotype diversity (Hd = 0.8899) but moderate nucleotide diversity (p = 0.00834), suggesting immune-driven balancing selection. The N-terminal region was highly conserved across isolates, including full conservation of the KLKQP motif, reinforcing its functional importance in hepatocyte invasion. In contrast, the central repeat region exhibited substantial variability in NANP/ NVNP tetrapeptide repeat numbers, and the C-terminal region, particularly the Th2R and Th3R epitopes showed extensive polymorphism. Notably, fewer than 1% of sequences matched the 3D7 vaccine strain, and several key amino acid positions associated with vaccine escape showed high mutation frequencies.DiscussionOur findings suggest that the genetic divergence of circulating csp variants in Kigali could be a factor influencing vaccine performance, underscoring the importance of ongoing molecular surveillance to guide eventual vaccine implementation in Rwanda and other endemic regions